Incision Wound Healing Activity of Red Betel Leaf (Piper crocatum) in Wistar Rats - Maharani Rizki Amanda Barokah; Tjandra, Lusiani; Andra Agnes Al Aska; Atik Sri Wulandari (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2026)
Background: Incisional wounds are tissue injuries that requireappropriate management to prevent complications. Red betelleaf (Piper crocatum) contains bioactive compounds with antiinflammatory, antioxidant, and antimicrobial properties thatmay enhance wound healing. Objective: This study aimed toevaluate the wound-healing activity of red betel leaf extract inWistar rats with incisional wounds. Methods: The research usedan experimental laboratory design in which test animals weredivided into five groups.: three treatment groups with extractconcentrations of 5%, 10%, and 15%, a positive control groupusing 10% povidone iodine, and a negative control group using0.9% NaCl. Observed parameters included redness, edema,exudate, granulation tissue formation, and wound lengthchanges during the healing process. Result: The resultsdemonstrated that Piper crocatum extract, particularly at aconcentration of 15%, significantly reduced inflammatory signs(erythema, edema, and exudate) and accelerated granulationtissue formation and wound contraction compared with thecontrol groups (p < 0.05). Conclusion: These findings suggestthat red betel leaf extract possesses pharmacological activitythat accelerates wound healing and has potential as acomplementary therapy in wound management.